EVALUASI BOD DAN COD DENGAN MENGGUNAKAN METODE QUAL2Kw DI SUNGAI PUDU KECAMATAN MANDAU KABUPATEN BENGKALIS PROVINSI RIAU - Ika Kusumawati (Journal of Environmental Engineering and Waste Management, 2016)
Pudu River that flow from Kota Duri which has a length of 26.04 km which is one of the rivers that flow in Kecamaan Saber and indicated many declined. One reason is the liquid waste that comes from the remnants of domestic waste water (domestic wastewater) and leachate (leachate) from the accumulation of garbage from several locations in Pudu River. This study aims to determine how the image quality of BOD and COD in Pudu River. The method used in this study with the primary survey (sampling), laboratory testing, and subsequent use QUAL2Kw program. The results obtained are: 1) the pollutant load of BOD, almost all the observation location above the threshold specified safe, except the observation location 5 (Bridges Tough Road I; Sub Pematang Pudu) is equal to 1,218 mg / l; and 2) the COD pollutant load in Pudu River, shows that at all locations on the above observations safe threshold. To anticipate is necessary to recover the quality of Pudu River, including: coordination between stakeholders in order to minimize the pollutant load, checking the presence / absence of wastewater before the wastewater discharged, the supervision of solid waste that are not disposed directly into Pudu River